Larval development of the blue crab Callinectes sapidus: effect of enriched rotifers as live food - Ospina-Salazar, Gloria Helena; Miranda-Baeza, Anselmo; Zea, Sven (Frontiers in Aquaculture, 2023)
Understanding nutrition and its effect on growth is essential for developing diets in commercially important species. This study aimed to evaluate the larval development of Callinectes sapidus fed with rotifers (Brachionus plicatilis) enriched with Chlorella pyrenoidosa (Ch) as a main protein source and a lipid emulsion (Spr) rich in highly unsaturated fatty acids. The enriched compositions had seven ratios Ch/Spr (w/w): 100/0, 90/10, 80/20, 70/30, 60/40, 50/50, and 40/60. The enriched rotifers with each ratio were called diets. Lipids increased progressively between 100/0 and 40/60 (7.48 to 11.30 g 100 g-1), as well as energy (21.88 to 23.16 kJ g-1), but the protein level did not show a clear trend (63.93 and 67.50 g 100 g-1). The production response of blue crab larvae showed significant differences within diets (P < 0.05). The highest survival (29 to 34%) was obtained in the 50/50 and 40/60 treatments. In the 40/60, 50/50, and 60/40 diets, the larval cycle was shorter (P < 0.05), and the megalopa stage was reached between 49 and 52 days of culture. Metamorphosis to megalopa occurred between the fifth and eighth molts; its corresponding weight varied from 0.72 to 1.33 mg, the length varied from 2,632 to 2,926 µm, and Le Cren´s condition factor varied from 0.83 to 1.16. The most important factor in the production response was the diet lipid content, which was significantly correlated with the survival, weight, length, and condition factor of C. sapidus larvae. Findings of the present study can be applied in future efforts towards mass culture of blue crab larvae in the Caribbean and can also potentially be used to study other crustacean species with similar characteristics.